Absolute levels of transcripts for mitochondrial uncoupling proteins UCP2, UCP3, UCP4, and UCP5 show different patterns in rat and mice tissues - Alán, Lukás; Smolková, Katarína; Kronusová, Eva; Santorová, Jitka; Jezek, Petr (Journal of bioenergetics and biomembranes, 2009)
Existing controversies led us to analyze absolute mRNA levels of mitochondrial uncoupling proteins (UCP1-UCP5). Individual UCP isoform mRNA levels varied by up to four orders of magnitude in rat and mouse tissues. UCP2 mRNA content was relatively high (0.4 to 0.8 pg per 10 ng of total mRNA) in rat spleen, rat and mouse lung, and rat heart. Levels of the same order of magnitude were found for UCP3 mRNA in rat and mouse skeletal muscle, for UCP4 and UCP5 mRNA in mouse brain, and for UCP2 and UCP5 mRNA in mouse white adipose tissue. Significant differences in pattern were found for rat vs. mouse tissues, such as the dominance of UCP3/UCP5 vs. UCP2 transcript in mouse heart and vice versa in rat heart; or UCP2 (UCP5) dominance in rat brain contrary to 10-fold higher UCP4 and UCP5 dominance in mouse brain. We predict high antioxidant/antiapoptotic UCP function in tissues with higher UCP mRNA content.
Keywords: messenger RNA; Membrane Transport Proteins; uncoupling protein 2; Rats; iontové kanály; Lung; Mitochondrial Membrane Transport Proteins; DNA primery; Uncoupling Protein 2; mozek; Mice; Mitochondrial Uncoupling Proteins; krysa rodu Rattus; Nerve Tissue Proteins; slezina; membránové transportní proteiny; polymerázová řetězová reakce s reverzní transkripcí; Mitochondrial Proteins; Brain; Uncoupling Protein 3; myokard; zvířata; plíce; RNA, Messenger; Myocardium; proteiny nervové tkáně; Species Specificity; myši; uncoupling protein 3; Ion Channels; Reverse Transcriptase Polymerase Chain Reaction; druhová specificita; mitochondriální odpřahující proteiny; DNA Primers; transportní proteiny mitochondriální membrány; Spleen; mitochondriální proteiny; Animals